PENGARUH EARNING MANAGEMENT DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Wi Rita Widya; Amelia Sandra (Akuntabilitas, 2014)
This study aimed to examine the effect of earnings management and corporategovernance mechanisms to proxy size of the board of commissioners, the proportion ofindependent commissioners, and the size of the audit committee on the disclosure ofcorporate social responsibility which are controlled by firm size and profitability. The theoryunderlying this research is stakeholder theory, legitimacy theory, agency theory, and signalingtheory. The sample is a mining company listed in the Indonesia Stock Exchange (BEI) for theperiod 2008-2011. The sampling technique used is Non-Probability Sampling using Judgement/purposive sampling. Analysis of test data using multiple regression. This research resulted infindings that earnings management and audit committee size does not significantly affect thedisclosure of social responsibility, while the size of the board of commissioners and theproportion of independent commissioners significant positive effect on social responsibilitydisclosure. However, company size and profitability are not proven to control the effects ofearnings management and corporate governance mechanisms on the disclosure of corporatesocial responsibility.DOI: 10.15408/akt.v7i1.2642